REDUCTION OF DEFECTIVE GOODS BY SLAG SHOT AND INCREASE OF RESISTANCE OF REFRACTORY AT APPLICATION OF PEARLITE ROCK - F. I. Majorov; A. V. Grishchenko; S. V. Kostrykin (Литьë и металлургия)
It is shown that application of fractionated pearlite rock leads to reduction of defective goods by slag shot and to increase of resistance of refractory facing up to 50%.